Persistent halogenated organic pollutants in follicular fluid of women undergoing in vitro fertilization from China: Occurrence, congener profiles, and possible sources. (January 2019) - Huang, Yumei; Yan, Muting; Nie, Huayue; Wang, Wenjing; Wang, Jun
Abstract: Analysis of persistent halogenated organic pollutants (HOPs) in human follicular fluid is important given previous reports of their adverse effects on the reproductivity of women. In the present work, HOPs, including polybrominated diphenyl ethers (PBDEs) and polychlorinated biphenyls (PCBs), were analyzed in 127 follicular fluid samples collected from patients who were undergoing in vitro fertilization in Central China. The concentrations of ∑7 BDEs (sum of BDE-28, -47, −99, −100, −153, −154, and −183) in follicular fluid ranged from not detected (n.d.) to 110 ng/g lipid weight (lw), with an average of 50 ± 24 ng/g lw. BDE-100 was suggested to be an indicator of BDE congeners in follicular fluid, with the highest concentrations and showing a significantly high correlation ( p < 0.01) with ∑7 BDEs. Penta-BDE products were the principal source of PBDEs in follicular fluid samples. The concentrations of ∑7 CBs (CB-28, -52, −101, −118, −138, −153, and −180) in follicular fluids ranged from n.d. to 250 ng/g lw, with an average of 77 ± 69 ng/g lw. CB-28 and CB-52 were considered to be indicator CB congeners, with tri-CBs and tetra-CBs dominating in follicular fluid. No significant correlation was observed between patient age and PBDE or PCB concentrations in follicular fluid, indicating that age was not the controlling factor influencing the bioaccumulation of most HOPs in this study. Graphical abstract: Image Highlights: Persistent halogenated organic pollutants (HOPs) in follicular fluid from China were analyzed. BDE-100 was suggested to be an indicator of BDE congeners. CB-52 and CB-28 were the major CB congeners. Age was not the controlling factor influencing HOP levels except for α-HCH and β-HCH. More attention to the adverse effects of HOPs on women's fertility in China is needed. Abstract : Occurrence and congener profiles of persistent halogenated organic pollutants (HOPs) were analyzed in follicular fluid from China.